Years of schooling and quality of governance: A case study from global data - Zaky, Ahmed (AUC Knowledge Fountain, 2016)
This paper examines the relationship between years of educational attainment and governance using panel data from 147 countries. The statistical model in this study analyzes the relationship between Average Years of Schooling, and the World Bank’s Worldwide Governance Indicators that represent governance exclusively. We assess whether average years of schooling can significantly predict governance when using controls and fixed effects. We also use average years of primary schooling, secondary schooling, and tertiary schooling to assess whether or not a change in a specific educational level; primary, secondary, or tertiary, shows more significance in relationship to quality of governance. Based on this initial analysis we find that years of educational attainment in at least one of the educational levels predict quality of governance. We also carry out a second analysis using the same statistical model but divide the initial dataset into three subsets; “Free”, “Partly Free”, and “Not Free” countries, based on the Freedom House categorization. The results indicate that educational attainment is only a predictor of quality of governance in the “Free” countries subset. This indicates the need to focus on statistical analysis of country subsets with similar “deeply-instilled attitudes,” as clarified by the revised version of modernization theory, in order to reach conclusive results.